El individuo como lugar de revelación. Líneas de diálogo entre la teología del monacato cristiano antiguo y el mundo contemporáneo (2021)
In the search for a possibility of spirituality in the contemporary world, the relationship that exists between the current conception of the individual with the basic anthropology of ancient Christian monasticism is discovered. For this reason, an approach is proposed to the personal capacities of the monk and they are related to the qualities of the contemporary individual. This link leads to a possibility of spirituality based on the personal capacities of the subject in search of a spiritual meaning for the human being in terms of integral well-being and fullness of life.